Pengaruh Pendapatan Usaha dan Biaya Operasional terhadap Laba Bersih Periode Triwulan I Tahun 2019-Triwulan I Tahun 2023: Studi Kasus pada PT Indo Pureco Pratama, Tbk - Helen, Helen; Marliani, Sari; Yuliawati, July (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to help companies determine the level of performance achieved in achieving net profit, their financial condition and the partial and simultaneous influence of business income and operational costs on net profit for the first quarter of 2019-first quarter of 2023 at PT Indo Pureco Pratama, Tbk. This study uses a quantitative analysis method with multiple linear regression analysis techniques using SPSS Version 24. The population is PT Indo Pureco Pratama, Tbk with a sample of financial reports for the period I quarter 2019-IV quarter 2023 with a sampling technique using purposive sampling.The study results descriptively explain that business income, operational costs and net profit of PT Indo Pureco Pratama, Tbk are in good condition during the period I quarter 2019-first quarter 2023. The results of the hypothesis test analysis show that partially business income has a positive and significant effect on net profit PT Indo Pureco Pratama, Tbk is proven by the calculated t value of 19.282 > 2.179 and a significant value of 0.000 < 0.05 and operational costs have a negative and significant effect on the net profit of PT Indo Pureco Pratama, Tbk proven by the calculated t value of -15.975 > 2.179 and the significant value 0.000 < 0.05 and simultaneously business income and operational costs have a positive and significant effect on the net profit of PT Indo Pureco Pratama, Tbk as evidenced by the calculated F value of 2698.620 > 4.75 and a significant value of 0.000 < 0.05.